Mismatch Between Anthropometric Measurements of Occupational Drivers in Southwest Nigeria and Vehicle Seat Design Parameters (International Journal of Scientific Research and Management (IJSRM), 2023)
Most commercial vehicles used for transportation are not manufactured in Nigeria. As a result, the design of these vehicles, which relies on anthropometric measurements from the manufacturing countries, does not adequately accommodate the variations in anthropometric measurements of Nigerian drivers. This mismatch can lead to ergonomic risk and musculoskeletal disorders. Therefore, this study investigated the level of mismatch between drivers’ anthropometric characteristics and seat design variables of selected commercial vehicles. A total of 161 male drivers were randomly selected, and data was collected using standard Nordic questionnaires. The anthropometric characteristics of the drivers were measured using a stadiometer and measuring tape. Seat design variables were also measured using a tape rule and steel rule. The collected data were subjected to statistical analysis, including the calculation of means, standard deviations, and 5th, 50th, and 95th percentiles of the anthropometric measurements. The results revealed the average anthropometric measurements for sitting height (erect), sitting height (normal), shoulder height, buttock-knee length, and buttock-popliteal length to be 83.01, 77.86, 52.71, 57.07, and 50.20 cm, respectively. Comparing the results of the seat variables with the relevant anthropometric characteristics, a mismatch in the measurements was observed. This led to the conclusion that the existing commercial vehicle seats in the Southwest region are not compatible with the anthropometric dimensions of the drivers.